Cultural heritage in international investment law and arbitration - Vadi, Valentina (Cambridge, UK : Cambridge University Press, 2014)
'Can states adopt protectionist cultural policies? What are the limits, if any, to state intervention in cultural matters? A wide variety of cultural policies may interfere with foreign investments, and a tension therefore exists between the cultural policies of the host state and investment treaty provisions. In some cases, foreign investors have claimed that cultural policies have negatively affected their investments, thereby amounting to a breach of the relevant investment treaty. This study maps the relevant investor-state arbitrations concerning cultural elements and shows that arbitrators have increasingly taken cultural concerns into consideration in deciding cases brought before them, eventually contributing to the coalescence of general principles of law demanding the protection of cultural heritage'--
'The original idea for this book came about in 2007 during the time I spent as a researcher at the European University Institute in Florence, Italy. Not only is Florence a world heritage site of ineffable beauty but it was also a financial capital during the Renaissance period, home to philosophical inquiry and capital flows, religious iconoclasm and supreme artistic expression, power struggles and influential political thinking'--
Machine generated contents note: 1. Cultural heritage in international law; 2. International investment law; 3. The World Heritage and foreign direct investment; 4. Underwater cultural heritage and foreign direct investment; 5. Cultural diversity, intangible heritage and foreign direct investment; 6. Indigenous cultural heritage and foreign direct investment; 7. Investing in culture.
Includes bibliographical references and index.
Keywords: Cultural property -- Protection (International law); Investments, Foreign (International law)